Kaizen Implementation in the Motorcycle Tire Testing Stage with the PDCA Cycle - Yuliarty, Popy; Sudibyo, Agung; Avrizal, Reza (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The research was conducted at the tire trial stage at a motorcycle tire production company, which aims to reduce defects in the measurement results at the tire sample trial stage. The company policy stipulates that tire trials are carried out on 10 tire samples taken at random from each of the total production of 250 motorcycle tires. From the samples taken, it was found that the types of tire defects were Cut Sample and Crown Sample as well as tire dimension defects that did not match the target with dimensional defect types namely Pattern Bare and Bead Crack with a total of 60% defects. The method used for improvement with Kaizen through the PDCA cycle, shows several improvement steps based on Fishbone Diagram and 5W1H analysis. The result of this research is the reduction of defects to zero defects (0%), which means that the company's quality objectives can be achieved. With the principle of Kaizen through this PDCA cycle, the company gets very satisfying results, in line with its target of zero defects.